FRAMING BERITA DAN INDEPENDENSI TVRI PADA PEMBERITAAN COVID-19 DI ERA NEW NORMAL - Permana, Gagah; Sindu, Jaka (Jurnal Insani, 2021)
This research studied how the Covid-19 news framing in the new normal era and TVRI independence in the "Jakarta Hari Ini" program. The research method used is a qualitative method with descriptive analysis. Data collection techniques using observation, interviews and documentation. Using a purposive sampling technique, the researcher selected two informants, namely the Producer and Coordinator of the Jakarta TVRI Coverage. Check the validity of the data using source triangulation and technical triangulation. Researchers analyzed several manuscripts of Covid-19 news in the new normal era of TVRI Jakarta to find out the framing made in the news using the analytical model of William A. Gamson and Modigliani. Researchers found that the framing made by TVRI Jakarta emphasized that the public could comply with every health protocol in carrying out activities outside the home to break the chain of spread of Covid-19 in DKI Jakarta. However, the researcher considers that in the case of Covid-19 reporting in the new normal era, TVRI Jakarta is not independent because it is not between the government and the community. This can be seen in the results of the analysis of the news script, which is more dominated by news from the government. This research can enrich media studies, in particular knowing the framing of Covid-19 news in the new normal era of TVRI Jakarta and its independence in reporting.